Health information provision, health knowledge and health behaviours: Evidence from breast cancer screening. (November 2020) - Eibich, Peter; Goldzahl, Léontine
Abstract : Many public health interventions aim to provide individuals with health information on the consequences of behaviours such as smoking, alcohol consumption or preventive care use, with the intention of changing health behaviour through better health knowledge. This paper examines whether the provision of health information in organised breast cancer screening programs affects mammography utilisation via changes in health knowledge. We use unique data on 10, 610 European women from the Eurobarometer survey collected in 1997/1998, and we exploit variation in the availability and coverage of organised breast cancer screening programs for causal identification in a difference-in-differences design. We find that health information provision improves health knowledge. Yet, these changes in health knowledge had little to no effects on mammography utilisation in the overall population. Our findings imply that health information provision contributes little to health behaviour change. Although screening programs are effective at increasing preventive care use, their effect can be attributed almost entirely to factors other than health knowledge. Highlights: We estimate a difference-in-differences model and conduct a mediation analysis. We exploit variation in screening program existence and eligibility ages in Europe. Screening program eligibility improves health knowledge about breast cancer. Changes in health knowledge contribute little to screening program uptake. Health information provision has a stronger impact on less educated women.